Ataxia Prevalence in Primary Orthostatic Tremor. (16th December 2020) - Thompson, Rebecca; Bhatti, Danish E.; Hellman, Amy; Doss, Sarah J.; Malgireddy, Kalyan; Shou, James; Srikanth-Mysore, Channaiah; Bendi, Sunil; Bertoni, John M.; Torres-Russotto, Diego
Background: The exact pathophysiology of primary Orthostatic Tremor (OT) is unknown. A central oscillator is assumed, and previous imaging studies show involvement of cerebellar pathways. However, the presence of ataxia on clinical exam is disputed. We set out to study ataxia in OT prospectively. Methods: EMG-confirmed primary OT subjects and spousal controls received a neurological exam with additional semiquantitative evaluations of ataxia as part of a multinational, prospective study. These included detailed limb coordination (DLC), detailed stance and gait evaluation (DS), and the Brief Ataxia Rating Scale (BARS). Intra- and inter-rater reliability were assessed and satisfactory. Results: 34 OT subjects (mean age = 67 years, 88% female) and 21 controls (mean age = 66 years, 65% male) were enrolled. Average disease duration was 18 years (range 4–44). BARS items were abnormal in 88% of OT patients. The OT subjects were more likely to have appendicular and truncal ataxia with significant differences in DLC, DS and BARS. Ocular ataxia and dysarthria were not statistically different between the groups. Discussion: Mild-to-moderate ataxia could be more common in OT than previously thought. This is supportive of cerebellar involvement in the pathophysiology of OT. We discuss possible implications for clinical care and future research. Highlights: Previous studies of Primary Orthostatic Tremor (OT) have proposed pathophysiologic involvement of the cerebellar pathways. However, presence of ataxia has not been systematically studied in OT. This is a prospective comprehensive ataxia assessment in OT compared to controls. Mild-to-moderate appendiculo-truncal ataxia was found to be common in OT.